Fatigue Characteritics of Medium Carbon Steel after Heat Treatment Using Sand as Cooling Media - Sunardi, Sunardi; Randu, Randu; Listijorini, Erny; Saefuloh, Iman; Notonegoro, Hamdan Akbar; Jannah, Miftahul (INTEK: Jurnal Penelitian, 2021)
Stress concentrations cause many machine element failures. Failure will occur more rapidly if the machine elements obtain repeated and fluctuating loading. For this reason, the material for machine elements must have better fatigue life. There are various attempts made to increase material life and other mechanical properties. In this study, the research sample used is AISI 4140 steel. The samples obtain hardening followed by cooling and tempering. The hardening temperature is 8500C with a holding time of 17 minutes. The cooling media in this research are dry sand, semi-wet sand, and wet sand. Wet measurements based on volumetric ratios. Semi-wet sand with a ratio of sand and water 4: 1, sandy sand 4: 2. The final process is tempering treatment, with a temperature of 2500C. The material fatigue test refers to the JIS Z 2274 Standard. From this study, the heat treatment given can reduce the fatigue life of the material, even though the hardness increases. The higher the cooling rate, the hardness of the material increases, but the fatigue life is low.